Effect of water activity and temperature on the growth of Eurotium species isolated from animal feeds. - Greco, Mariana; Pardo, Alejandro; Pose, Graciela; Patriarca, Andrea (Revista Iberoamericana de Micologia, 2018)
Background Xerophilic fungi represent a serious problem due to their ability to grow at low water activities causing the spoiling of low and intermediate moisture foods, stored goods and animal feeds, with the consequent economic losses. Aims The combined effect of water activity and temperature of four Eurotium species isolated from animal feeds was investigated. Methods Eurotium amstelodami , Eurotium chevalieri , Eurotium repens and Eurotium rubrum were grown at 5, 15, 25, 37 and 45 °C on malt extract agar adjusted with glycerol in the range 0.710–0.993 of water activities. Results The cardinal model proposed by Rosso and Robinson (2001) was applied to fit growth data, with the variable water activity at fixed temperatures, obtaining three cardinal water activities ( a w min , a w max , a w opt ) and the specific growth rate at the optimum a w ( μ opt ). A probabilistic model was also applied to define the interface between growth and no-growth. The cardinal model provided an adequate estimation of the optimal a w to grow and the maximum growth rate. The probabilistic model showed a good performance to fit growth/no-growth cases in the predicted range. Conclusions The results presented here could be applied to predict Eurotium species growth in animal feeds.